Penerimaan Diri Ibu Anak Down Syndrome Melalui Bimbingan Keagamaan Di Desa Sekar Biru - Yanasari, Pebri (Department of Islamic Guidance and Counseling, 2025)
The results of this study are: 1) Islamic The results of this study are: 1) Islamic religious guidance followed by mothers who have children with Down Syndrome has an important role in providing psychological and emotional support. This guidance is carried out through religious studies, religious study groups, individual consultations and social activities, self-reflection, and religious studies organized by local religious figures. This activity helps mothers understand that every child is a mandate from Allah and has its own special qualities; 2) The benefits of Islamic religious guidance for self-acceptance of mothers who have children with Down Syndrome provide various significant benefits. Through this guidance process, mothers not only gain religious knowledge, but also emotional and social support which is very important in self-acceptance of mothers. These benefits include: increased spiritual understanding, providing much-needed emotional support, being more active in spiritual practices, such as praying and dhikr, changes in mothers' attitudes and perceptions of their children, providing mothers with new skills in childcare, and family involvement. This research uses a qualitative approach that focuses on understanding phenomena, actions, and behaviors through the presentation of descriptive data in the form of words or writing. KEYWORDS: Maternal Self-Acceptance, Child Down Syndrome, Religious Guidance